Hygroscopic expansion of self-adhesive resin cements and the integrity of all-ceramic crowns. Issue 8 (August 2018) - Kirsten, Magdalena; Matta, Ragai Edward; Belli, Renan; Lohbauer, Ulrich; Wichmann, Manfred; Petschelt, Anselm; Zorzin, José
Abstract: Objective: Low pH neutralization and subsequent remnant hydrophilicity can lead to hygroscopic expansion of self-adhesive resin cements (SARCs) after water storage. The aim of this in vitro study was to investigate the effects of hygroscopic expansion of SARCs, used as luting and partial core build-up material, on integrity and cement gap thickness increase of all-ceramic CAD/CAM crowns. Methods: Human third molars (n = 48) were prepared and anatomical all-ceramic CAD/CAM crowns were manufactured (VITABLOCS Mark II, VITA Zahnfabrik). Crowns internal surfaces were HF etched and silanized. The prepared teeth with their respective crowns were divided into 6 groups (n = 8). In groups 1, 3 and 5 the coronal dentin was removed to simulate a partial core build-up. Groups 1 and 2 were luted with iCEM (Heraeus Kulzer), 3 and 4 with RelyX Unicem 2 Automix (3M), 5 and 6 with Variolink Esthetic DC (Ivoclar Vivadent). All specimens were dual cured and stored in distilled water at 37 °C. Crown integrity was controlled at baseline and in regular intervals until 180 days. Cement gap thickness was measured using an optical 3D scanner (ATOS Triple scan, GOM) at baseline and after 180 days. Crown integrity was statistically analysed using Kaplan–Meier survival analysis and cement gap thickness increase using two-way ANOVA ( α = 0.05). Results: After 180 days storage, crack formation was observed in all specimens of group 1 (mean survival time of 85.5 days), in one specimen of group 2 and in two specimens of group 4. Two-way ANOVA analysis revealed a statistically significant interaction between material type and build-up on cement gap size increase for iCEM. Significance: Within the limits of this study, the application of SARCs with low pH neutralization as partial build-up material under CAD/CAM crowns is not recommended for clinical use.